2022
DOI: 10.3389/fgene.2022.996364
|View full text |Cite
|
Sign up to set email alerts
|

Clinical genetics of spondylocostal dysostosis: A mini review

Abstract: Spondylocostal dysostosis is a genetic defect associated with severe rib and vertebrae malformations. In recent years, extensive clinical and molecular diagnosis advancements enabled us to identify disease-causing variants in different genes for such severe conditions. The identification of novel candidate genes enabled us to understand the developmental biology and molecular and cellular mechanisms involved in the etiology of these rare diseases. Here, we discuss the clinical and molecular targets associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…The Uncx4.1 gene is not necessary for somite segmentation but serves to maintain condensation of the caudal half of newly formed somites and sclerotomes. As mouse and human cases with spondylocostal and spondylothoracic dysostosis accumulate and undergo detailed gene study, it becomes clear that even within the seven gene-specific mutations affecting the Notch and temporal segmentation pathways currently identified each specific gene is affected by differing types of mutations including nonsense, missense, small deletion and small insertion changes ( Cornier et al, 2008 ; Otomo et al, 2019 ; Umair et al, 2022 ). To the Notch pathway (or pathway-related) gene with a mutation causing axial abnormality and the slightly differing temporal abnormalities induced we can also add, as a third cause in many groups, the type and position of the mutation within the pathway gene involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Uncx4.1 gene is not necessary for somite segmentation but serves to maintain condensation of the caudal half of newly formed somites and sclerotomes. As mouse and human cases with spondylocostal and spondylothoracic dysostosis accumulate and undergo detailed gene study, it becomes clear that even within the seven gene-specific mutations affecting the Notch and temporal segmentation pathways currently identified each specific gene is affected by differing types of mutations including nonsense, missense, small deletion and small insertion changes ( Cornier et al, 2008 ; Otomo et al, 2019 ; Umair et al, 2022 ). To the Notch pathway (or pathway-related) gene with a mutation causing axial abnormality and the slightly differing temporal abnormalities induced we can also add, as a third cause in many groups, the type and position of the mutation within the pathway gene involved.…”
Section: Discussionmentioning
confidence: 99%
“…Several Notch pathway genes underlying the segmentation clock controlling normal embryonic somitogenesis have been identified ( Dequéant and Pourquié, 2008 ; Krol et al, 2011 ; Saga, 2012 ). Mutations in the Dll3 and other segmentation clock pathway genes have been demonstrated to lead to axial malformations in both mouse and human disorders of the spondylocostal dysostosis skeletal dysplasia group ( Turnpenny et al, 2017 ; Nóbrega et al, 2021 ; Umair et al, 2022 ). While both the normal molecular pathways of the segmentation clock and mutations in the Dll3 and other Notch pathway genes leading to axial malformations have been outlined in detail in numerous studies, specific supramolecular structural studies of the step-by-step pathogenesis of the malformations have not been done.…”
Section: Introductionmentioning
confidence: 99%
“…Seven genotypes have been identified that affect the notch signalling pathway. [8] Genetic testing is now available in our country, but only in a few private centres such as our institution, and it takes several weeks to get results. The tests are costly at USD300 - 2 000, and as they are self-financed, many families are unable to afford them.…”
Section: Editorialmentioning
confidence: 99%
“…Interestingly, there are many more documented human DLL3 clinical mutations ( versus DLL1 ) that result in a disorganized vertebral column. To date, there have been 28 reported DLL3 mutations resulting in a form of spondylocostal dysostosis (SCDO), SCDO1, which is a type of vertebral malformation ( Kusumi et al, 2004 ; Umair et al, 2022 ). On the other hand, there has been only 1 DLL1 mutation causing another type of SCDO, SCDO7 ( Barhoumi et al, 2019 ).…”
Section: Species-specific Divergent Functions Of Notch Ligands and Re...mentioning
confidence: 99%
“…Furthermore, because this gene swapping was limited to a BAC construct extending only up to the 3′ UTR of the neighboring gene Per1 , one cannot exclude the possibility of cis -elements downstream of Hes7 affecting its periodicity. While there are only limited reports on how the segmentation clock and the circadian clock could interact genetically ( Umair et al, 2022 ), the PER1 gene also displays an in-phase gene oscillation phenotype with HES7 in human PSM cells in vitro ( Matsuda et al, 2020b ).…”
Section: Insights From Non-classical Model Systems and Future Perspec...mentioning
confidence: 99%